A Multi-Actor Multi-Criteria Analysis of the Performance of Global Cities - Karima Kourtit; Cathy Macharis; Peter Nijkamp (Tinbergen Institute, 2013)
The strong world-wide urbanisation trend calls for a repositioning of cities, especially the large cities with a global impact. These cities tend to become economic, logistic and political powerhouses and are increasingly involved in a competition on their integral performance. The present paper aims to trace to what extent and why some cities outperform others. Starting from an extensive database on many important characteristics of global cities, this paper offers a multi-criteria methodology for identifying the relative position of various important cities on the basis of distinct assessment criteria. The explicit consideration of the perceptions of important classes of stakeholders on the performance outcomes of the various cities involved allows for a enhanced policy analysis. From a technical assessment perspective, the applied part of the paper employs the MAMCA and PROMETHEE multi-criteria methodology, which have proven their analytical power in various mu lti-criteria evaluation problems over the past years. The paper concludes with some policy perspectives and lessons.
Keywords: C03; 330; Urbanisation; global cities; multi-criteria analysis; performance; stakeholders; MAMCA; PROMETHEE; GAIA